Lagerstroemia Tree, St. Anns, Port of Spain, Trinidad, B.W.I. - Guppy, Patricia Lechmere (My University, 2009)
Photo depicts a large Lagerstroemia tree located in St. Anns, Port of Spain, with a few cattle grazing under it.
Colour: Green, Yellow, Lilac, Brown; Style: Portrait; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Plants--Trinidad and Tobago; Lagerstroemia--Trinidad and Tobago; Plants, Ornamental--Trinidad and Tobago; Crape myrtle, Common--Trinidad and Tobago